Production Function Analyze For Almansoor General Company For Engineering Industries In Iraq - عبد الكريم, خالد طه (Journal of Economics and Administrative Sciences, 2012)
The production function forms one of the techniques used in evaluation the  production the process for any establishment or company, and to explain the importance of contribution of element from the independent variable and it's affect on the dependent variable. Then knowing the elements which are significant or non-significant on the dependent variable.    So the importance of this study come from estimating the Cobb-Douglas production function for Al- Mansoor General Company for Engineering industries in Iraq during the period (1989-2001)     To explain the importance which effects the independent variable such as (No. of employees, wages and salaries paid and the value of requirements of investment) on the dependent variable (the value of output and the gross value added) by using ordinary least square method and then collecting and analyzing the results by using Econometrics program (Gretl 1.8.0) and finally concluding the main recommendations and presenting the main procedures